Efeitos de suplementação nutricional oral intradialítica em pacientes idosos - Bertoni, Vanessa Maria (2023)
Patients with chronic kidney disease who undergo renal replacement therapy in the form of hemodialysis have a higher caloric and protein demand due to losses during the dialysis process, to avoid the process of weight loss, common in this population. The objective was to evaluate the effects of specific oral nutritional supplementation on the nutritional status in elderly patients on hemodialysis. A longitudinal before-and-after study was conducted to assess the effect of using a specific nutritional supplement for chronic kidney disease during hemodialysis sessions. The study included elderly patients of both sexes who have been undergoing renal replacement therapy in the form of hemodialysis for at least three months, with four-hour sessions, on alternate days, three times a week. The intradialytic intervention period corresponded to 90 days, on the days of hemodialysis sessions, which were on a three-times-a-week scale. The group was supplemented with a specific formula for chronic kidney patients. Anthropometric measurements were performed after hemodialysis sessions and on the arm without venous access, when it involved measurement in the limb. The weight measurement was collected from the patients' medical records. The data were analyzed using the Student t-test for paired samples, Wilcoxon W, Friedman, and general linear model for repeated measures. The significance level is 0.05. Regarding the nutritional status, in the pre-intervention evaluation with the use of supplementation, eutrophy was prevalent, followed by overweight and underweight. After the intervention, an increase in dry weight and a decrease in oscillation amplitudes were identified. Among the nutrients analyzed in the food recall, values of kilocalories below the estimates of nutritional needs were observed both before and after the intervention. The specific oral nutritional supplement, offered in an intradialytic way, brought benefits to the nutritional status and improvement in the stabilometric parameters to elderly patients on hemodialysis